Albatross : Their World, Their Ways - De Roy, Tui; Jones, Mark; Fitter, Julian (Collingwood, Vic. CSIRO, 2008)
The albatross is a creature of legend, of poetry and of dreams. It is the ultimate nomad, whose sailplane wings - the longest of any living bird - harness the shrieking winds of the southern ocean as it glides around the globe. This master of wind and wave is also the subject of intense scientific scrutiny and fascinating revelations. But just as we are discovering the magic of these glorious birds, they are becoming increasingly threatened; today, over three-quarters of all albatross species are edging towards extinction.
Include Color Illustrations, Map, Glossary and Index.
Their World, Their Ways.
Keywords: Albatrosses -- Albatrosses - Pictorial works -- Albatrosses - Conservation